PENGGUNAAN ARANG TEMPURUNG KELAPA SEBAGAI BAHAN TAMBAH CAMPURAN BETON MUTU BETON Fc’ 14,53 MPa - Syafyudin, Buyung Adnan; Rizal, rizal; Rusfiandi, wandi (RETENSI, 2021)
Concrete is a construction material that has been commonly used for buildings. Concrete is formed from mixed aggregate (fine aggregate and coarse aggregate) plus other materials, namely cement, water, and other added materials with a certain ratio value. This study uses an added material in the form of coconut shell charcoal in a concrete mixture to determine whether it can improve the quality of the compressive strength of concrete. The uses of added material is taken from the percentage by weight of cement used. The use of coconut shell charcoal as an added ingredient is 2.5%, 5%, 7.5% and 10%. The results of the compressive strength of 28 days of concrete using coconut shell charcoal with a variation of the addition of 2.5% is 18.30 MPa, 5% is 17.86 MPa, 7.5% is 19.03 MPa, and 10% is 18.50 MPa. Based on the result above, the highest compressive strenght value is equal to 7.5%, so it can be concluded that the addition of coconut shell charcoal to the concrete mix can increase the compressive strength.